If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7x + -6) = 3(1 + -3x) Reorder the terms: 2(-6 + 7x) = 3(1 + -3x) (-6 * 2 + 7x * 2) = 3(1 + -3x) (-12 + 14x) = 3(1 + -3x) -12 + 14x = (1 * 3 + -3x * 3) -12 + 14x = (3 + -9x) Solving -12 + 14x = 3 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. -12 + 14x + 9x = 3 + -9x + 9x Combine like terms: 14x + 9x = 23x -12 + 23x = 3 + -9x + 9x Combine like terms: -9x + 9x = 0 -12 + 23x = 3 + 0 -12 + 23x = 3 Add '12' to each side of the equation. -12 + 12 + 23x = 3 + 12 Combine like terms: -12 + 12 = 0 0 + 23x = 3 + 12 23x = 3 + 12 Combine like terms: 3 + 12 = 15 23x = 15 Divide each side by '23'. x = 0.652173913 Simplifying x = 0.652173913
| 45+63x(45+55)33-88= | | 5.4=18y | | 5.4/2y=9 | | (9)w=54 | | 2.5(-3x+2)=.75x+6 | | 4(4+1)=x+10 | | X+12+17=5x-14 | | 10(-12x+8)=3x+6 | | 57(4q)=288 | | 5x-14-17=x+12 | | 5x-3x=25 | | 16x+24=15x-18 | | 2(5x+7)=8x-6 | | -5(9y+4)= | | 45x^2+90x+25=0 | | 100/370=h/740 | | 0.2x+1.5=0.1 | | 5/15=12/n | | 35x^2+67x+30=0 | | 6x+12y=36 | | 84-5x=40+24 | | 5/n=25/35 | | 6/7=n/35 | | -117-7x=8x++18 | | s=68-20log(0+1) | | 9w-18=48 | | s(t)=68-20log(0+1) | | 8x+24=28 | | 7+11i/i | | 6x+6-5x-7=27 | | 6x+6=5x-7 | | 6x+6+27=5x-7 |